KONTRIBUSI ILMU BIOMEKANIKA TERHADAP PENINGKATAN KETERAMPILAN MOTORIK SISWA DALAM PEMBELAJARAN PJOK - Ahmad Mursyidin Mursyidin; Kasmiati Kasmiati; Ahmad Muhaeming Muhaeming; Arman Arjuna Arjuna; Edi Kurniawan urniawan (STKIP Subang, 2026)
Physical Education, Sports, and Health (PJOK) plays an important role in developing students' motor skills through various physical activities. One of the scientific approaches that can support the improvement of motor skills is biomechanics, which examines human movement based on mechanical principles. This study aims to analyze the contribution of biomechanics to the improvement of students' motor skills in PJOK learning. The study employed a qualitative descriptive approach using a literature review method. Data were collected through relevant references related to biomechanics, motor skills, and PJOK learning. The analysis was conducted through the stages of data identification, classification, evaluation, and synthesis. The results indicate that the application of biomechanical principles supports the improvement of movement quality, body coordination, balance, movement efficiency, and mastery of basic motor skills. Biomechanics also helps students understand proper movement techniques, reduce movement errors, and perform physical activities more safely. The integration of biomechanical principles in PJOK learning can support more effective learning processes and optimize the development of students' motor skills. Keywords: Biomechanics, Motor Skills, Physical Education, Movement Learning, PJOK